SEED BANK IN TWO SITES OF SEMIDECIDUOUS SEASONAL FOREST IN VIÇOSA, MINAS GERAIS - Braga,Antonio Jorge Tourinho (2016)
ABSTRACT Aimed of this study was examine, describe and confronted the floristic composition and the density the seed bank in two successional stages of Seasonal Semideciduous Forest, in Viçosa, MG. Forty soil samples total in two distinct period (drought station finish and rainy station finis) and arranged for germinate in wooden boxes (0,5 x 0,5 x 0,1 m) in shading of 60%. The individual germination in each valuation epoch was compared utilizing the t test for independent samples; the test indicated one individual plants germination major in seed bank levy intermediary between epoch drought station finis and rainy station. Hundred nine taxons were sampled in the seed bank the forest altogether, 101 species were identified as belonging to 73 genera distributed among 40 families, 56 species commonness in two successional stages of forest and 49 species commonness of two levy period. Asteraceae was the families with the largest number of species as initial forest much as advanced forest, in both period of valuation. The herbaceous individuals predomination in all forests and valuation epoch, whit not representation the fragility of the seed bank.